Concurrent chemoradiotherapy degrades the quality of life of patients with stage II nasopharyngeal carcinoma as compared to radiotherapy - Pan, Xin-Bin (Oncotarget, 2017)
The purpose of this study was to compare the quality of life (QoL) of stage II nasopharyngeal carcinoma (NPC) patients treated with radiotherapy (RT) versus concurrent chemoradiotherapy (CCRT). In a cross-sectional study, these patients were treated with RT (n = 55) or CCRT (n = 51) between June 2008 and June 2013. For all subjects, disease-free survival was more than 3 years. QoL was assessed using the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-Core 30 (EORTC QLQ-C30) questions and the Head and Neck 35 (EORTC QLQ-H&N35) questions. RT had better outcomes than CCRT for global QoL, functional scales, symptom scales of fatigue and insomnia, financial problems, and weight gain. Survivors receiving 1 cycle of concurrent chemotherapy had worse QoL outcomes than survivors receiving 2 cycles of concurrent chemotherapy. Patients receiving 3 cycles of concurrent chemotherapy had the best QoL outcomes. Thus, CCRT adversely affects the QoL of patients with stage II NPC as compared to radiotherapy.